Co‐occurring medical conditions in adults with Down syndrome: A systematic review toward the development of health care guidelines. Part II. Issue 7 (27th April 2020) - Capone, George; Stephens, Mary; Santoro, Stephanie; Chicoine, Brian; Bulova, Peter; Peterson, Moya; Jasien, Joan; Smith, Anna Jo; ,
Abstract: Adults with Down syndrome (DS) represent a unique population who are in need of clinical guidelines to address their medical care. Many of these conditions are of public health importance with the potential to develop screening recommendations to improve clinical care for this population. Our workgroup previously identified and prioritized co‐occurring medical conditions in adults with DS. In this study, we again performed detailed literature searches on an additional six medical conditions of clinical importance. A series of key questions (KQ) were formulated a priori to guide the literature search strategy. Our KQs focused on disease prevalence, severity, risk‐factors, methodologies for screening/evaluation, impact on morbidity, and potential costs/benefits. The available evidence was extracted, evaluated and graded on quality. The number of participants and the design of clinical studies varied by condition and were often inadequate for answering most of the KQ. Based upon our review, we provide a summary of the findings on hip dysplasia, menopause, acquired cardiac valve disease, type 2 diabetes mellitus, hematologic disorders, and dysphagia. Minimal evidence demonstrates significant gaps in our clinical knowledge that compromises clinical decision‐making and management of these medically complex individuals. The creation of evidence‐based clinical guidance for this population will not be possible until these gaps are addressed.